Inovasi Tanpa Batas : Kolaborasi Perempuan Wirausaha Dalam Menciptakan Produk Dan Jasa Baru Pada Era Teknologi 5.0 - Khori Pujianto; Titis Tata; Dinda Arum Melati; Nasrullah Umar (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2025)
Technology 5.0 is the most recent evolution of technology, which connects the physical and digital worlds more integratively and effectively. This era marks a significant change in the way technology is integrated into human life. In creating new innovations in this technological era, female entrepreneurs have an important role. Through collaboration which includes cross-sector cooperation, network development and the use of technology, we can encourage economic growth that is inclusive and relevant to modern human life. This research provides evidence that initiatives led by women have high adaptability and tend to produce innovations that are more humane and user-oriented. In this way, collaboration between women entrepreneurs not only strengthens their role in the economy, but also enriches the innovation ecosystem in the technology 5.0 era.